1988
DOI: 10.1007/bf01907265
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the response of venous smooth muscle to arterial endothelium-derived relaxing factor (EDRF) in respect of the role of nitric oxide

Abstract: In bioassay and organ bath experiments, the responses of different canine venous preparations to arterial and their own EDRF were studied. Vena jugularis, vena femoralis and vena mesenterica relaxed on both EDRFs released by acetylcholine. Vena saphena, venae cordis and vena portae did not show endothelium-dependent dilation, either under bioassay or in organ bath experiments. All the veins tested relaxed completely after sodium nitroprusside administration. The identity of EDRF and nitric oxide is not confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Results of animal studies have suggested that NO activity is heterogenous between different venous preparations. 6,7 For example, Vedernikov et al 6 demonstrated marked endothelium-dependent relaxation in jugular, femoral, and mesenteric veins but found this was absent in the saphenous, portal, and inferior caval veins, despite preservation of endotheliumindependent relaxation in response to sodium nitroprusside.…”
Section: Role Of No In the Regulation Of Vascular Tonementioning
confidence: 99%
See 2 more Smart Citations
“…Results of animal studies have suggested that NO activity is heterogenous between different venous preparations. 6,7 For example, Vedernikov et al 6 demonstrated marked endothelium-dependent relaxation in jugular, femoral, and mesenteric veins but found this was absent in the saphenous, portal, and inferior caval veins, despite preservation of endotheliumindependent relaxation in response to sodium nitroprusside.…”
Section: Role Of No In the Regulation Of Vascular Tonementioning
confidence: 99%
“…This is consistent with the findings of animal studies that demonstrated heterogeneity between different venous preparations. 6,7 It is the veins of the capacitance bed that predominantly determine overall venous tone. Therefore, our finding of both stimulated and basal NO activity in capacitance veins provides compelling new evidence that NO contributes to the regulation of venous tone and to resting venous tone in human health.…”
Section: Validation Of Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that NO activity varies between different venous preparations. Vedernikov et al (38) demonstrated marked endothelium-dependent relaxation in jugular, femoral, and mesenteric veins. However, such activity was not observed in the saphenous, portal, or inferior cava veins, despite preservation of endothelium-independent relaxation in response to SNP.…”
Section: Veins and Vascular Tone Control: Role Of Nomentioning
confidence: 99%
“…19 In addition, neither the spectrophotometric method nor the chemiluminescence method (using an acidic reducing reflux chamber) for detection of NO can distinguish it from nitrite or labile nitroso species; although the former method actually determines the concentration of NO2 derived from oxidation of NO, use of a reducing acidic refluxing chamber with the chemiluminescence method results in reduction of NO2 and nitroso compounds to NO and elimination of the high specificity for NO. Thus, neither method can determine whether the initial EDRF was NO2 or a labile nitroso substance converted to NO or whether EDRF itself was free NO.…”
mentioning
confidence: 99%